PERBAIKAN FASILITAS DAN MANAJEMEN MESJID NURUL HIKMAH DESA BUMI AYU SOLOK SELATAN BERSAMA TIM PENGABDIAN KEPADA MASYARAKAT POLITEKNIK NEGERI PADANG - Yuli Yetri; Nasirwan Nasirwan; Rakiman Rakiman; Haris Haris; Saif Hadid Alkhairi (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
To maximize the function of the mosque as a place of worship, a community service team has carried out together in the form of counseling and donations. This is done because mosques have a very strategic function in Islamic society, both as places of worship and as media centers for holistic development of the people. This service team is trying to optimize the function of the mosque as a center for community empowerment activities. This community service is motivated by the facilities and infrastructure of the Nurul Hikmah mosque which are still inadequate for the needs and comfort of worship, such as: carpets, loudspeakers, mosque clocks, towers and pulpits. Even the implementation of mosque management has not been so evenly distributed so that it has not been accompanied by social welfare efforts for the community. The purpose of this service is to find out the condition of the social welfare of the community. Community Service is the third dharma of higher education tri dharma. Meanwhile, in analyzing the data, the writer uses data collection, data reduction, data presentation, and verification. The results of this service showed that the condition of community welfare is experiencing stability with the implementation of programs carried out by mosque administrators to help community welfare, then the implementation of mosque management in an effort to improve community social welfare is by having a clear and transparent management function which makes the function of the mosque better.